The advertising campaign of recycling machine / Nurzainah Mohd Arbawi - Mohd Arbawi, Nurzainah (Faculty of Art and Design, 2013)
If posed a question to our society these days about what is recyclable? Sure many are able to answer it. For the purpose of more accurate, recycling is the process of treating waste materials to produce new products. Realizing this, many related to recycling campaigns have been implemented by government agencies or NGOs. Recycling is a key component of waste management in modern times. Some of the wastes that can be recycled include aluminum, plastic and newspapers. Aluminum is a material that can be recycled 100%. According to the facts, the aluminum can be reused within 60 days after recycling. RECYCLING means collecting and sorting of solid waste for the purpose of producing, the other meaning is to treat things that have already been used so that they can be used again (from Oxford dictionary). Machine means a piece of equipment with moving parts that is designed to do a particular job (from Oxford dictionary). RECYCLING MACHINE is the machine for recycle such as paper and plastic. This recycling machine used a card to trace point when student use it when they want recycle. By means of the use of this card can attract the attention of children or students to recycle every day. Also, at this stage can increase the sense of competition in them since child.